PERCEPTION OF YOUNG CONSUMERS ON KHADI IN THE PANIPAT DISTRICT, HARYANA - MONIKA ROHILLA *; ANAMIKA GAUTAM (The Journal of Research ANGRAU, 2022)
The main aim of this research was to analyse the knowledge and awareness level of youth regarding the khadi fabric in the district of Panipat, Haryana. The study carried out the relationship between characteristics of both buying behaviour and its acceptability among youth. A totalof 292 adults, between the age of 18 and29 years, were selected as respondents. It was reported that 62% of youth, did not find khadi clothing a pocket-friendly option. It was seen that 40% of consumers were aware of only cotton khadi and 56% accepted it for its high comfort value. Similarly, 70% of respondents felt that khadi fits all age groups. It was noticed that nearly 20% of youth were not using or buying khadi at all. It was also observed that nearly 20% of the respondents preferred khadi to be used in home textiles only such as draperies, bed linens, blanket covers, etc.Whereas, 62% of youth felt khadi clothing was expensive. It was concluded that consumers were having a positive attitude towards khadi. It was noticed that along with comfort, youth prefer fashionable clothing that is relatively cheap.